Small-incision access retroperitoneoscopic technique (SMART) pyeloplasty in adult patients: comparison of cosmetic and post-operative pain outcomes in a matched-pair analysis with standard retroperitoneoscopy: preliminary report - Pini, Giovannalberto; Gözen, Ali Serdar; Schulze, Michael; Fiedler, Marcel; Klein, Jan; Rassweiler, Jens (World journal of urology, 2011)
ObjectivesTo present small-incision access retroperitoneoscopic technique pyeloplasty (SMARTp), a novel mini-laparoscopic approach for management of uretero-pelvic junction obstruction (UPJO) in adults including comparison with the standard retroperitoneoscopic technique (SRTp).MethodsIn a non-randomised study, we matched 12 adult patients treated from August to November 2010 by SMARTp with 12 patients treated with SRTp from January to November 2010. Mini-laparoscopic retroperitoneal space was created with a home-made 6-mm balloon trocar. One 6-mm (for 5-mm 30° telescope) and two 3.5-mm trocars (for 3-mm working instrument) were used. SRTp was performed with 11- and 6-mm trocar. Primary endpoints included evaluation of cosmetic appearance and post-operative pain evaluated respectively by the patient and observer scar assessment scale (POSAS) and analogue visual scale (VAS). Secondary endpoints were comparison between operative and functional parameters.ResultsCosmetic cumulative results were statistically significant in favour of SMARTp (POSAS: 37.9 vs. 52.4; P = 0.002). A better trend has been shown by post-operative pain (first to fourth day VAS), although not statistically significant (4.2 vs. 4.9, P = 0.891). No differences were recorded in terms of operative time, pre- and post-operative Hb difference, DJ-stent removal and resistive index (RI) improvement. The SMARTp group showed a faster drain removal (2.4 vs. 3.4 day, P = 0.004) and discharge (4.5 vs. 5.4 day P = 0.017).ConclusionsPreliminary data support SMARTp as safe procedures in experienced hands, providing better cosmetic results compared to SRTp. Further studies and clinical randomised trial performed in a larger population sample are requested.
Published online: 23 August 2011
Gesehen am 25.10.2018